The geotechnical challenges of tidal turbine projects - Small, Andrew A.; Cook, Greg K.; Brown, Michael J. (Volume 9A: Ocean Renewable Energy, 2014)
Tidal energy projects offer a predictable renewable energy source. Therefore several sites around the coast of the United Kingdom (UK) have been identified to have the potential to host multiple array turbine developments that could be used to generate upwards of 100MW each. However, the high tidal energy environment required to provide the input to tidal power devices present a combination of design and installation challenges to developers and engineers. Whilst the water depths are comparable to offshore oil and gas projects in the southern North Sea, tidal energy projects present significantly different seabed and associated geotechnical challenges that require novel solutions. Concerns have been expressed regarding the design of turbine base structures, which is often based upon typical nearshore/offshore soil sampling and geotechnical laboratory testing techniques that are often inappropriate for the seabed materials encountered. This issue is further compounded by the design constraints imposed on the base structure foundations (e.g. tripod gravity base structures). These include strict leveling tolerances required for efficient turbine operation, and which require a detailed understanding of seabed bathymetry at each turbine location where multiple seabed contact points may be required. In addition to the tidal energy turbines, inter-array cables that connect the turbines and export cable routes which distribute the power to shore also present their own design and installation challenges. It is often overlooked, but significant uncertainty lies in the definition of cable corridors with respect to the seabed materials. In many cases burial may be considered as a means of product protection where seabed conditions allow. This paper aims to examine the geotechnical issues associated with the difficult seabed and environmental conditions present at typical tidal turbine sites in the UK and globally in an attempt to offer some potential solutions. These issues typically include; difficulties in performing site ...